Effectiveness and cost-effectiveness analysis of 11 treatment paths, seven first-line and three second-line treatments for Chinese patients with advanced wild-type squamous non-small cell lung cancer: A sequential model - Zhao, Mingye; Shao, Taihang; Chi, Zhuoyuan; Tang, Wenxi (Frontiers in Public Health, 2023)
Background A total of 11 treatment sequences for advanced wild-type squamous non-small cell lung cancer are recommended by Chinese Society of Clinical Oncology Guidelines, consisting of seven first-line and three second-line treatments, five of them were newly approved in China between 2021-2022. We evaluated the effectiveness and cost-effectiveness of these strategies from the Chinese healthcare system perspective. Methods Using network meta-analysis with non-proportional hazards for relative efficacy. A sequential model was developed to estimate costs and quality-adjusted life years (QALY) for treatment sequences with first-line platinum- and paclitaxel-based chemotherapy (SC) with or without nedaplatin, tislelizumab, camrelizumab, sintilimab, sugemalimab or pembrolizumab, followed by second-line docetaxel, tislelizumab or nivolumab. QALY and incremental cost-effectiveness ratio (ICER) were used to evaluate effectiveness and cost-effectiveness, respectively. Cost-effective threshold was set as USD 19,091. Subgroup analysis was conducted to determine the best first-line and second-line therapy. Results Pembrolizumab+SC, followed by docetaxel (PED) was the most effective treatment sequence. QALYs for patients received SC, nedaplatin+SC, tislelizumab+SC, sintilimab+SC, camrelizumab+SC, sugemalimab+SC, pembrolizumab+SC followed by docetaxel were 0.866, 0.906, 1.179, 1.266, 1.179, 1.266, 1.603, 1.721, 1.807; QALYs for SC, nedaplatin+SC followed by tislelizumab were 1.283, 1.301; QALYs for SC, nedaplatin+SC followed by nivolumab were 1.353, 1.389. Camrelizumab+SC, followed by docetaxel (CAD) was the most cost-effective. Compared to SC with or without nedaplatin, tislelizumab, or sintilimab followed by docetaxel, ICERs of CAD were USD 12,276, 13,210, 6974, 9421/QALY, respectively. Compared with nedaplatin or SC followed by tislelizumab, the ICERs of CAD were USD 4183, 2804/QALY; CAD was dominant compared with nedaplatin or SC followed by nivolumab; The ICER of sugemalimab+SC followed by docetaxel and PED were USD 522,023, 481,639/QALY compared with CAD. Pembrolizumab+SC and camrelizumab+SC were the most effective and cost-effective first-line options, respectively; tislelizumab was the most effective and cost-effective second-line therapy. Tislelizumab used in second-line was more effective than first-line, no significant differences between their cost-effectiveness. Sensitivity and scenario analysis confirmed robustness of the results. Conclusions PED and CAD are the most effective and cost-effective treatment sequence, respectively; pembrolizumab+SC and camrelizumab+SC are the most effective and cost-effective first-line choice, respectively; tislelizumab is the most effective and cost-effective second-line choice.